2018
DOI: 10.14366/usg.18019
|View full text |Cite
|
Sign up to set email alerts
|

Application of contrast-enhanced ultrasound for evaluation of thyroid nodules

Abstract: Contrast-enhanced ultrasound (CEUS) is widely used to evaluate tumor microcirculation, which is useful in the differential diagnosis between benignity and malignancy. In the last 10 years, the applicability of CEUS to thyroid nodules has greatly improved due to technological refinements and the development of second-generation contrast agents. In this review, we summarize the applications of CEUS for thyroid nodules, focusing on the imaging findings of malignant and benign nodules in the existing literature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 50 publications
2
50
0
3
Order By: Relevance
“…Hypoenhancement and heterogeneity describe malignant lesions, while homogeneity and the presence of an enhanced peripheral ring indicate a benign nodule. However, more research is necessary in this promising field [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoenhancement and heterogeneity describe malignant lesions, while homogeneity and the presence of an enhanced peripheral ring indicate a benign nodule. However, more research is necessary in this promising field [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…US-guided lung biopsy has success rate similar to CT-guided biopsies (which is the gold standard) in the assessment of the cyto-histological diagnosis of peripheral lung lesions, but offers lower complications, less time, and less cost without radiation exposure (Frongillo et al, 2018;Sperandeo et al, 2019). A new US contrast agent, SonoVue, (Bracco SpA), has emerged in recent years for USguided biopsy of lesions of the liver (D'Onofrio et al, 2015), thyroid (Zhan and Ding, 2018), and mediastinal cancers (Fu et al, 2016), but it has also been proposed, off label, for the study of peripheral lung lesions in contact with the pleural surface (Cao et al, 2011;Dong et al, 2015;Sidhu et al, 2018).…”
Section: A Commentary Onmentioning
confidence: 99%
“…New-generation contrast agents (SonoVue) are administered intravenously and contain sulfur hexafluoride microbubbles that stay in the blood flow for a while. The examiner focuses the US image on the ROI and a contrastenhanced image is displayed, detecting microvascular changes in the lesion that classic Doppler cannot display [80].…”
Section: Contrast-enhanced Ultrasound (Ceus)mentioning
confidence: 99%
“…In studies where CEUS was performed on thyroid lesions, malignity was indicated by hypoenhancement and heterogeneity [80]. Hypoenhancement can be explained by the absence of blood supply in the central area of the tumor, due to thrombus formation, vascular compression, and necrosis.…”
Section: Contrast-enhanced Ultrasound (Ceus)mentioning
confidence: 99%